The First Amendment's religion clauses: the Calvinist document that interprets them both - Farish, Leah (The journal of religion & society, 2010)
This paper suggests that the Westminster Confession of Faith's provisions about church and state, revised in Philadelphia at the start of the Constitution's ratifying convention, furnished much of the syntax and vocabulary for the First Amendment's religion clauses. Recognizing the cultural links between the new American government and the Presbyterian Church, the author argues that it was natural for the founders to look to how the new Westminster Confession situated church and state. The author argues that Fisher Ames's proposed wording for the First Amendment won immediate adoption because it resonated with the Confession, standing as it did in that culture for unity and good sense.